Hypertransfusion Therapy in Sickle Cell Disease in Nigeria - Adewoyin, Ademola Samson (Hindawi Publishing Corporation, 2014)
Introduction. Hypertransfusion refers to chronic blood transfusion therapy aimed at ameliorating disease complications in various haemopathies particularly the haemoglobinopathies. In sickle cell disease, hypertransfusion is aimed at maintaining patient's haemoglobin level at 10 to 11 g/dL using haemoglobin AA blood and its resultant dilutional effect on sickle haemoglobin is sustained by intermittent long-term transfusions. Aim and Objective. This paper highlights hypertransfusion and its privileged position as a secondary measure in prevention and treatment of sickle cell disease, especially in the Nigerian context. Materials and Methods. Relevant literatures were searched on PubMed, Google Scholar and standard texts in haematology and transfusion medicine. Keywords used in the search are hypertransfusion, sickle cell disease, chronic transfusion, and Nigeria. Literatures gathered were reviewed, summarized, and presented in this paper. Result. Immense clinical benefit is associated with hypertransfusion therapy including prevention of stroke and amelioration of severe sickle cell disease especially in transplant ineligible patients. Careful patient selections, appropriate blood component, and prevention of transfusion hazards as well as oversight function of an experienced haematologist are pertinent to a successful hypertransfusion therapy. Conclusion. Improved knowledge of the benefits and practice of hypertransfusion will effectively translate into improved health status even among Nigerian sickle cell disease patients.